2014
DOI: 10.1371/journal.pone.0085784
|View full text |Cite
|
Sign up to set email alerts
|

Functional Annotation of Rheumatoid Arthritis and Osteoarthritis Associated Genes by Integrative Genome-Wide Gene Expression Profiling Analysis

Abstract: BackgroundRheumatoid arthritis (RA) and osteoarthritis (OA) are two major types of joint diseases that share multiple common symptoms. However, their pathological mechanism remains largely unknown. The aim of our study is to identify RA and OA related-genes and gain an insight into the underlying genetic basis of these diseases.MethodsWe collected 11 whole genome-wide expression profiling datasets from RA and OA cohorts and performed a meta-analysis to comprehensively investigate their expression signatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…81–85 Indeed, the recent Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of OA and control samples provide evidence that inflammation signals contribute to OA pathogenesis through cytokine-induced mitogen-activated protein (MAP) kinases, NF-κB activation, and oxidative phosphorylation. 86 …”
Section: Etiologymentioning
confidence: 99%
“…81–85 Indeed, the recent Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of OA and control samples provide evidence that inflammation signals contribute to OA pathogenesis through cytokine-induced mitogen-activated protein (MAP) kinases, NF-κB activation, and oxidative phosphorylation. 86 …”
Section: Etiologymentioning
confidence: 99%
“…Elevated systemic inflammation was also observed in obesity mice with DMM surgery, including cytokine and chemokine production, synovial tissue expansion, inflammatory cell infiltration, and NF-κB pathway activation (59), suggesting obesity plays a role during PTOA development. Indeed, recent transcriptomic analyses provide evidence that inflammatory signals contribute to OA pathogenesis through cytokine-induced MAP kinases, NF-κB activation, and oxidative phosphorylation (60). …”
Section: Epigenetic and Inflammatory Changes In Oamentioning
confidence: 99%
“…As a result, NF-κB function impacts multiple cellular outcomes, including cell migration, proliferation, differentiation, and survival (77). While controlled NF-κB-mediated responses promote homeostasis, persistently elevated responses of this pathway are associated with diseases such as rheumatoid arthritis (RA) and OA (60,78). Despite the large body of evidence on the role of TAK1-IKK2-NF-κB axis in these diseases, the mechanisms by which pathologic activity of NF-κB induces joint catabolism are largely unknown.…”
Section: Homeostatic and Pathologic Nf-κb Signaling In The Skeletal Smentioning
confidence: 99%
“…The activation of the ULK1 complex requires the initiation of autophagy, which has been shown to be the most upstream step of autophagosome formation. Previous studies have reported that autophagy and its anti-inflammatory function contribute to both inflammatory and autoimmune diseases, such as systemic lupus erythematosus,27 rheumatoid arthritis and osteoarthritis 28. In these disease processes, autophagy could affect the selection of thymic T cell, antigen processing, cross presentation, cell survival and cytokine responses of immune cells 29.…”
Section: Discussionmentioning
confidence: 99%